SKOPOS THEORY: A PRACTICAL APPROACH IN THE TRANSLATION PROCESS - Ika Kana Trisnawati (Englisia: Journal of Language, Education, and Humanities, 2014)
Numerous criticisms have been addressed toward the application of Skopos theory within translation studies. Issues such as vague concepts of translation, ‘dethroning’ the source text, oversimplification and inapplicability to achieve equivalence for literary and religious texts are some of many critiques for Skopos theory. In addition, from a student’s perspective, it is argued that there is no specific guideline to carry out the theory. However, here, I would like to present my perspective as a student practicing translation as well as a brief overview of Skopos theory, its criticisms as well as its usefulness in actual implementation.